2016
DOI: 10.1159/000431328
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Young's Modulus of Collagen Fibrils from Expanded Skin Using Anisotropic Controlled Rate Self-Inflating Tissue Expander

Abstract: Mechanical properties of expanded skin tissue are different from normal skin, which is dependent mainly on the structural and functional integrity of dermal collagen fibrils. In the present study, mechanical properties and surface topography of both expanded and nonexpanded skin collagen fibrils were evaluated. Anisotropic controlled rate self-inflating tissue expanders were placed beneath the skin of sheep's forelimbs. The tissue expanders gradually increased in height and reached equilibrium in 2 weeks. They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 43 publications
4
9
1
Order By: Relevance
“…Figure 5e reveals that tumors with higher collagen density are stiffer than those with lower collagen density. This observation is consistent with previously reported research obtained with invasive measurement techniques (Manssor et al 2016; Seifert et al 2014). However, to our knowledge, this is the first reported study that used imaging to demonstrate that orthotopically grown tumors are stiffer than subcutaneously grown tumors because of differences in collagen density.…”
Section: Discussionsupporting
confidence: 94%
“…Figure 5e reveals that tumors with higher collagen density are stiffer than those with lower collagen density. This observation is consistent with previously reported research obtained with invasive measurement techniques (Manssor et al 2016; Seifert et al 2014). However, to our knowledge, this is the first reported study that used imaging to demonstrate that orthotopically grown tumors are stiffer than subcutaneously grown tumors because of differences in collagen density.…”
Section: Discussionsupporting
confidence: 94%
“…In this report, we have observed that aging leads to an increase in the elastic modulus of dentinal collagen, associated with higher MGO levels in the organic matrix. The distribution of collagen modulus data is consistent with previous reports and reflects the biological variability of complex tissue samples (Manssor et al 2016; Calò et al 2020). Indeed, AGE accumulation has been shown to increase the YM of collagen in tissue and in vitro experiments (Verzijl et al 2002; Depalle et al 2015; Panwar et al 2015; Schuh et al 2021), suggesting that the increase in elasticity observed in PT and IT collagen is mediated by the accumulation of MGO adducts and other potential AGEs and crosslinks (Lederer and Bühler 1999).…”
Section: Discussionsupporting
confidence: 91%
“…34 Tissue-scale measurements of sections of sheep skin collagen were shown to be 35.2 ± 27 MPa for fibers of diameters 106.7 ± 28.5 nm. 35 The rat-tail collagen is an anisotropic structure containing triple helical collagen fibers arranged into fibrils, which impart the high elastic modulus to the structure. On the other hand, the PCL fibrous matrices are isotropic with random fibers leading to a reduction in the elastic modulus of the fiber mats.…”
Section: Resultsmentioning
confidence: 99%